Conjunctive Adverbials Used in Popular Scientific Articles - Ani Malichatun; Tofan Dwi Hardjanto (Deskripsi Bahasa, 2020)
Cohesion is an essential component of discourse that will help the readers comprehend the articles’ flow idea. Conjunctive adverbial is one of the cohesive devices that is commonly used in academic proses. This research aims to observe the forms, the sentential positions, and the cohesive meaning of conjunctive adverbials. Popular scientific articles are chosen to be data sources. The articles were downloaded from scientific magazines. Eighteen articles were from National Geography, and forty-six articles were from Psychology Today. Corpus linguistics is used as the approach of this study. The data are processed using Wordsmith 4 apps. The data selected are tabulated in Ms. Excel and analyzed using cohesion theory suggested by Halliday and Hasan (1976). The results show that conjunctive adverbials are dominated in word forms and followed by phrase forms in both magazines. The sentential positions of conjunctive adverbials are most frequently placed in an initial position followed by the magazines’ medial positions. The end position of conjunctive adverbials is not found. The most frequent conjunctive adverbial function is adversative, and the least frequent is causal in both magazines.